Interrater reliability of the Volume-Viscosity Swallow Test; screening for dysphagia among hospitalized elderly medical patients. (December 2017) - Jørgensen, Lise Walther; Søndergaard, Kasper; Melgaard, Dorte; Warming, Susan
Summary: Background: Oropharyngeal dysphagia (OD) is prevalent among medical and geriatric patients admitted due to acute illness and it is associated with malnutrition, increased length of stay and increased mortality. A valid and reliable bedside screening test for patients at risk of OD is essential in order to detect patients in need of further assessment. The Volume-Viscosity Swallow Test (V-VST) has been shown to be a valid screening test for OD in mixed outpatient populations. However, as reliability of the test has yet to be investigated in a population of medical and geriatric patients admitted due to acute illness, we aimed to determine the interrater reliability of the V-VST in this clinical setting. Reporting in this study is in accordance with proposed guidelines for the reporting of reliability and agreement studies (GRRAS). Methods: In three Danish hospitals (CRD-BFH, CRD-GH, NDR-H) 11 skilled occupational therapists examined an unselected group of 110 patients admitted to geriatric or medical wards. In an overall agreement phase raters reached ≥80% agreement before data collection phase was commenced. The V-VST was applied to patients twice within maximum one hour by raters who administrated the test in an order based on randomization, blinded to each other's results. Agreement, Kappa values, weighed Kappa values and Kappa adjusted for bias and prevalence are reported. Results: The interrater reliability of V-VST as screening test for OD in patients admitted to geriatric or medical wards was substantial with an overall Kappa value of 0.77 (95% CI 0.65–0.89) however interrater reliability varied among hospitals ranging from 0.37 (95% CI −0.01 to 0.41) to 0.85 (95% CI 0.75–1.00). Interrater reliability of the accompanying recommendations of volume and viscosity was moderate with a weighted kappa value of 0.55 (95% CI 0.37–0.73) for viscosity and 0.53 (95% CI 0.36–0.7) for volume. The overall prevalence of OD was 34.5%, ranging from 8% to 53.6% across hospitals. The prevalence and bias adjusted Kappa value (PABAK) was 0.76 (range 0.6–0.85). Mean time to perform the test was 13.1 min (SD 6.924). Conclusions: The V-VST seems to be a moderately reliable screening tool for detecting OD among medical and geriatric patients. However, the recommendations of volume and viscosity add limited clinical value to the test.